Analysis of the Association between Fast Food on Oral Health and Hygiene - A Survey - Baala vignesh. A1 , Karthik Ganesh Mohanraj2 , Ravindra Kumar Jain3 (Institute of Medico-legal Publications Pvt Ltd, 2020)
Health is a state of complete physical, mental and social well being of an individual and not merely theabsence of disease or immunity status of an individual. An unhealthy diet is proven to implicate many riskfactors for the incidence of oral diseases. Thus, there are various health education programs to educatepeople on the importance of a proper healthy diet, thereby reducing the incidence of oral diseases prevailingbecause of an unhealthy diet. Thus, this survey was done to evaluate the awareness of people towardsmaintaining a proper healthy diet. This study was done to check the awareness of people towards the riskfactors and impacts of fast food on the oral health status of a person. This is a questionnaire based survey.An online questionnaire was shared among 100 dental students in Chennai. Based on the answers fromthe survey, the data was compiled and analyzed and based on the results of the survey, the responses wereanalysed through statistical analysis software SPSS version 20.0. The results of the study showed that 90%of the individuals who took part in the survey consumed fast food, out of which 78% of them were nonvegetarians. 91% of them were aware of the complications of having an unhealthy diet and what risk factorsit possessed to the oral health of an individual. 40% of the individuals consume fast food at least once aweek. 77% knew the causative reasons for the incidence of dental caries in an individual. Within the limitsof the study, the study results showed that most individuals who took part in the survey consume food fromfast food and they weren’t aware of the impacts of unhealthy nutrition and bad hygiene measures. Thissurvey had created an impact on the individuals by educating them on the benefits of having a healthy dietand proper hygiene.